PENGARUH KOMPETENSI, INDEPENDENSI, PROFESIONALISME TERHADAP KUALITAS AUDIT - Rudi Hartono (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2017)
This study aimed to test whatever there is influence of Competence, Independence, Professionalism, Integrity, and Objectivity of the Quality Audit. The study was conducted by distributing questionnaires. The study population was Affiliates Medium Public Accountants and Public Accounting Firm Medium Non Affiliates. Data analysis is done using multiple regression. The result showed that the competence, independence, professionalism, integrity and objectivity  affect audit quality on an ongoing basis. In addition, this study proves that the partial competency, independence and Professionalism while simultaneously all influence the quality of audits. For research in the future, this study suggests the development of survey area coverage and the addition of more variables that affect audit quality